Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap OCB Karyawan di Hotel Bukit Indah Lestari Baturaja - Hilmi Wiranawata; Jenny Afriyanti (Universitas 17 Agustus 1945 Semarang, 2024)
This study aimed to determine the influence of job satisfaction and organizational commitment on organizational citizenship behavior (OCB) of employees at the Bukit Indah Lestari Baturaja Hotel. The data analysis technique used was Multiple Linear Regression. Based on the results of the partial analysis there was an influence of job satisfaction on organizational citizenship behavior (OCB) of employees at the Bukit Indah Lestari Baturaja Hotel with at-count (4.878) > t-table ( 2.009). Organizational commitment variable had an influence on organizational citizenship behavior (OCB) of employees at the Bukit Indah Lestari Baturaja Hotel with t count (4.716) > t-table (2.009). Simultaneously, it was found that there was an influence of job satisfaction and organizational commitment on organizational citizenship behavior (OCB) of employees at Bukit Indah Lestari Baturaja Hotel with f-count (45.555) > f-table (3.187). The coefficient of determination (R2) obtained was 0.650. This showed that the contribution of the influence of job satisfaction and organizational commitment to organizational citizenship behavior (OCB) was 65% while the remaining 35% was influenced by other variables not mentioned in this study such as personality, motivation, morals and organizational culture (Widyaninngrum, 2019: 102 ).